2021
DOI: 10.1038/s41684-021-00831-x
|View full text |Cite
|
Sign up to set email alerts
|

Annelid genomes: Enchytraeus crypticus, a soil model for the innate (and primed) immune system

Abstract: Enchytraeids (Annelida) are soil invertebrates with worldwide distribution that have served as ecotoxicology models for over 20 years. We present the first high-quality reference genome of Enchytraeus crypticus, assembled from a combination of Pacific Bioscience single-molecule real-time and Illumina sequencing platforms as a 525.2 Mbp genome (910 gapless scaffolds and 18,452 genes). We highlight isopenicillin, acquired by horizontal gene transfer and conferring antibiotic function. Significant gene family exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 109 publications
1
7
0
1
Order By: Relevance
“…Indeed, similar results were previously reported from the analysis of a sub-set of the data (Zn EC50 for 4 days) reported here (Castro-Ferreira et al, 2014). It has been suggested that ionic stabilizers have probably a key role in maintaining homeostasis in enchytraeids (Amorim et al, 2021). The plasticity of enchytraeids to survive in aquatic biotopes, such as marine interstitial environments, may be explained by dealing with the level of salts that is much higher than in terrestrial soil environments.…”
Section: Gene Expressionsupporting
confidence: 88%
See 1 more Smart Citation
“…Indeed, similar results were previously reported from the analysis of a sub-set of the data (Zn EC50 for 4 days) reported here (Castro-Ferreira et al, 2014). It has been suggested that ionic stabilizers have probably a key role in maintaining homeostasis in enchytraeids (Amorim et al, 2021). The plasticity of enchytraeids to survive in aquatic biotopes, such as marine interstitial environments, may be explained by dealing with the level of salts that is much higher than in terrestrial soil environments.…”
Section: Gene Expressionsupporting
confidence: 88%
“…Our results point towards the increase in inflammatory response, which emerged associated to DNA damage mechanisms. The recently sequenced genome of E. crypticus (Amorim et al, 2021) shows that the innate immune system (and response to stress) is among the most expanded gene families.…”
Section: Gene Expressionmentioning
confidence: 99%
“…Starting with the common processes, one of the mostly affected was the lipid metabolic process (affected by nano_ATZ_EC10 and EC50_3d and 7d; ATZ_EC10_7d; Gesaprim_EC10_3d and 7d, Gesaprim_EC50_3d) with the up-regulation of several cytochrome P450 family transcripts ( e.g. 2R1 and 2D15) and carbonyl reductase coding genes [the cytochrome P450 gene family is among the expanded gene families identified in the E. crypticus genome 43 ]. Based on the KEGG pathway analysis, this is in line with the effects on the arachidonic acid metabolism (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The recognition of pathogens by pattern recognition receptors (PRRs) triggers type I interferons (a central event of the immune response against viral infection) and signalling pro-inflammatory cytokines cascades ( García-Sastre and Miorin, 2016 ). TRIM proteins, expanded in E. crypticus ( Amorim et al, 2021 ), are essential and act as restriction factors or by modulating PRR signalling. Curiously, SARS-CoV-2 has been observed to disable interferons – “strikingly depressed interferon activity and elevated chemokines in individuals whose disease became severe and critical” ( Wadman, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The ACE gene has been identified in the soil model Enchytraeus crypticus; the genome of this species was recently sequenced ( Amorim et al, 2021 ) and revealed important gene family expansions, among which the innate immune system e.g. via the ACE-2 receptor.…”
Section: Introductionmentioning
confidence: 99%